The effect of calcium intake on body weight in pregnant women from South Africa, Zimbabwe and Argentina participating in the Calcium and Pre-eclampsia trial - Cormick, Gabriela (Department of Human Biology, 2020)
Introduction: The prevalence of overweight and obesity is increasing worldwide. It has been estimated that every kilogram of weight gain during adulthood represents a 3% to 6% risk increased of cardiovascular disease. There are some studies showing an inverse relationship between calcium intake and body weight. Overweight and obese women are advised to lose weight before conception, however the evidence on how to achieve this is scarce. No studies have investigated the effect of calcium supplementation on weight management before conception or during pregnancy. Aims and objectives: The overarching purpose of this project was to provide information and enrich the body of evidence of the effect of calcium intake on body weight. The first aim was to evaluate the effect of calcium intake on body weight of fertile or pregnant women; secondly to investigate the pre-pregnancy weight status, weight gain during pregnancy and adequacy of dietary intake of pregnant women participating in the Calcium and Pre-eclampsia (CAP) trial. The third aim was to perform a systematic review of studies evaluating the effect of calcium intake on body weight. I was part of the core research team throughout the CAP trial duration and also lead the nutritional component. The trial sample size included 540 pregnant women recruited between 2012 and 2017 in South Africa, Zimbabwe and Argentina. Women were randomized pre-pregnancy to receive 500 mg of elemental calcium or placebo until 20 weeks´ gestation, whereafter they received 1500 mg. Weight was measured pre-pregnancy and at 8, 20 and 32 weeks’ gestation. Diet was assessed at 20 weeks´ gestation. Ethical approval was obtained from appropriate national and institutional ethical review bodies as applicable for each study site. Results: There was a high proportion of women who started their pregnancy overweight or obese (73.7% in South Africa and 60.2% in Zimbabwe). Most women had an inadequate intake of micronutrients at 20 weeks pregnancy. For the most basic micronutrients like iron, calcium, folate and zinc, the percentage of women with intakes below requirements was above 90%. Although there was no effect of calcium supplementation on body weight in the sample of the CAP trial, the calcium group had a no statistically significant smaller increase in body weight during pregnancy especially in those who were obese at the start of the trial. The systematic review shows a small but statistical effect of calcium supplementation in body weight (Mean Difference (MD) -0.33 kg, 95% CI -0.57 to -0.09); (p=0.007); 819 participants; 15 studies) and in BMI (MD -0.17, 95% CI -0.21 to -0.13); p < 0.00001; 695 participants; 10 studies). Conclusion: We found a high prevalence of obesity found together with the micronutrient inadequacy which show a very poor nutritional status of women who have the possibility of getting pregnant again. This needs to be addressed so that maternal and perinatal outcomes are improved. There is a need to implement nutritional counselling preconceptionally to these women before they fall pregnant. The results of this thesis show a no statistically significant smaller increase in body weight in women supplemented with calcium, opening a promising area of research for weight management including the study of the mechanisms involved. Before making clinical recommendations further studies are needed with higher sample size to have the power to detect clinically significant effects.